2019
DOI: 10.4274/tjh.galenos.2018.2018.0190
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide for the Management of Bleeding Episodes in Patients with Hereditary Hemorrhagic Telangiectasia: Effects on Epistaxis Severity Score and Quality of Life

Abstract: Hereditary hemorrhagic telangiectasia (HHT) is a rare autosomal dominantly inherited disorder characterized by bleeding episodes. These episodes tend to happen spontaneously and reduce the quality of life. Patients are often unresponsive to local measures. With the pathophysiological role of angiogenesis in HHT, antiangiogenic drugs including thalidomide are used to control bleeding episodes. In our study, we evaluated 6 patients with HHT, calculating their Epistaxis Severity Score (ESS) and performing a quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Thus, episodes of epistaxis can significantly alter the psychosocial QOL of patients [ 43 ]. Because of these irregular, spontaneous and above all unpredictable manifestations, it is essential to pay particular attention to this area that is central to QOL of HHT patients [ 7 , 13 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, episodes of epistaxis can significantly alter the psychosocial QOL of patients [ 43 ]. Because of these irregular, spontaneous and above all unpredictable manifestations, it is essential to pay particular attention to this area that is central to QOL of HHT patients [ 7 , 13 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are two oral, targeted antiangiogenic agents with multiple published studies describing effectiveness and safety in treating bleeding in HHT: pazopanib 18,19 and thalidomide. [20][21][22][23][24][25] Doxycycline, an oral tetracycline antibiotic, has antiangiogenic potential owing to its ability to inhibit matrix metalloproteinases; however, a recent randomized, controlled trial of doxycycline for bleeding in HHT was unambiguously negative, finding no improvement in any of the primary or secondary endpoints for doxycycline over placebo. 26 Because antiangiogenic therapy in HHT typically requires long-term administration to maintain effectiveness and thalidomide may cause potentially irreversible peripheral neuropathy (a risk that increases with longer durations of treatment), 27 the authors only consider use of thalidomide when other agents are ineffective, contraindicated, or inaccessible.…”
Section: Oral Targeted Antiangiogenic Therapies For Bleeding Manageme...mentioning
confidence: 99%
“…Other systemic therapies including beta blockers or estrogens could be used on an individualized basis. Randomized studies have found promising results with tacrolimus and thalidomide [ 54 , 55 , 56 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Thalidomide treatment in HHT patients was associated with less red packed blood transfusion, decreased frequency of iron deficiency anemia, lower scores on the ESS, and thus improving the quality of life. Recent evidence shows that thalidomide makes blood vessels of HHT patients firmer and less prone to breaking [ 54 , 55 ].…”
Section: Treatmentmentioning
confidence: 99%